การพัฒนารูปแบบการเรียนรู้ด้วยการนำตนเองสำหรับนักศึกษาวิทยาลัยชุมชน - ชินพงษ์ อุไรวรรณ; พูลสุวรรณ ศิริยุภา (Journal of Research and Curriculum Development, 2012)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อพัฒนารูปแบบการเรียนรู้ด้วยการนำตนเองสำหรับนักศึกษาวิทยาลัยชุมชน โดยใช้วิธีการวิจัยเอกสาร (Documentary Research) ผลการวิจัยพบว่า แนวทางในการพัฒนารูปแบบการเรียนรู้ด้วยการนำตนเองสำหรับนักศึกษาวิทยาลัยชุมชน จำเป็นต้องใช้แนวคิดของทฤษฎีการเรียนรู้ของผู้ใหญ่ แนวคิดการเรียนรู้ด้้วยการนำตนเอง แนวคิดการพัฒนาการเรียนรู้ด้วยการนำตนเองด้วยการคิดอภิมาน และแนวคิดการประเมินการเรียนรู้ของผู้ใหญ่รูปแบบการเรียนรู้ด้้วยการนำตนเองที่ได้จากการสังเคราะห์งานวิจัยและเอกสารที่เกี่ยวข้อง ประกอบด้วยการเรียนรู้ 7 ขั้นตอน ได้แก่ ขั้นตอนที่ 1 วิเคราะห์ตนเอง ขั้นตอนที่ 2 ออกแบบการเรียนรู้ ขั้นตอนที่ 3 ดำเนินกิจกรรมการเรียนรู้ ขั้นตอนที่ 4 นำเสนอผลการเรียนรู้ ขั้นตอนที่ 5 สังเคราะห์ความรู้ ขั้นตอนที่ 6 ตรวจสอบผลการเรียนรู้ และขั้นตอนที่ 7 สะท้อนผลการเรียนรู้ The Development of Self-Directed Learning Model for Community College Students This research aims to develop the self-directed learning model for the community college students by using the documentary research. The results of this research revealed that the self-directed learning model for community college students must be based on the adult learning theories, self-directed learning, meta-cognition and assessment of adult learning. The self-directed learning model from the synthesis of research papers and journal articles was composed of 7 steps: 1) analyzing learner by themselves 2) designing a learning plan 3) acting learning activities 4) presenting learning outcomes 5) synthesizing knowledge 6) evaluating learning outcomes, and 7) reflecting learning outcomes.